2011
DOI: 10.1084/jem.20110236
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ– and IL-10–expressing virus epitope-specific Foxp3+ T reg cells in the central nervous system during encephalomyelitis

Abstract: Pathogen-specific Foxp3+ T reg cells can be identified on the basis of cytokine production, are detected in naive T cell populations, and exhibit suppressive ability toward effector T cells with the same antigen specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
111
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(121 citation statements)
references
References 26 publications
9
111
1
Order By: Relevance
“…Our data also suggest that nTreg could contribute directly to the pathogenesis via the production of IFN-␥ and to a lesser extent IL-4, both of which are associated with ECM (7,44). Although never described in ECM, this observation is in line with two recent reports describing the polarization of Treg into IFN-␥-producing Th1 cells following acute infection by Mycobacterium tuberculosis (45) and Toxoplasma gondii (46) and in other inflammatory settings (47)(48)(49)(50)(51). In addition, nTreg plasticity was associated with a modulation of their transcription program (expression of T-bet and possible downregulation of Foxp3) (45-47, 51, 52).…”
Section: Discussionsupporting
confidence: 91%
“…Our data also suggest that nTreg could contribute directly to the pathogenesis via the production of IFN-␥ and to a lesser extent IL-4, both of which are associated with ECM (7,44). Although never described in ECM, this observation is in line with two recent reports describing the polarization of Treg into IFN-␥-producing Th1 cells following acute infection by Mycobacterium tuberculosis (45) and Toxoplasma gondii (46) and in other inflammatory settings (47)(48)(49)(50)(51). In addition, nTreg plasticity was associated with a modulation of their transcription program (expression of T-bet and possible downregulation of Foxp3) (45-47, 51, 52).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, it has been described that Foxp3 ϩ Treg cells may coexpress transcription factors typical of effector TH1, TH2, and TH17, such as Tbet, GATA3, and Stat3 (26)(27)(28). The expansion of these T regulatory subsets is driven by the TH cytokines (IFN-␥, IL-4, IL-17) and occurs in parallel with the related effectors (27,38), and, in definite pathological conditions, such as strong pathogen-induced immunopathology, it was reported that these Treg cells also produce the TH-related cytokines (39,40) without losing the regulatory ability. With these premises, it is conceivable that Treg cells acquire (or reacquire) the TH1 phenotype, with the expression of Tbet and also the production of IFN-␥, in response to the great amounts of IFN-␥ released under the influence of MDDC-PfSE.…”
Section: Discussionmentioning
confidence: 99%
“…During MHV infection, virus-specific CD4 + T cells can acquire a Treg phenotype (42). Thus, the interpretation that Tregs can selectively contribute to immune privilege of CNS self-antigens during viral infection whereas the initiation of protective T cell responses remains unaltered raises the question of how such selectivity is achieved.…”
Section: Discussionmentioning
confidence: 99%